The Role of Brand Image in Mediating the Influence of Social Media Marketing on Purchase Intention - I Made Bagus Mas Ramaditya; Ni Nyoman Kerti Yasa (International Journal of Management Research and Economics, 2024)
The creative industry, particularly the fashion sector, has significantly impacted Indonesia's economy, with sports sneakers serving not only as footwear but also as an essential part of fashion and global trends. Adidas, as one of the leading sneaker manufacturers, ranked first in the sports shoes category at the 2024 Top Brand Award. This research aims to examine and explain the role of brand image in mediating the influence of social media marketing on purchase intention among prospective Adidas sports sneaker consumers in Denpasar. The sample size in this study was 112 respondents, and data collection was conducted through a questionnaire. The collected data were analyzed using classical assumption tests, path analysis techniques, and mediation role testing. The results of this study indicate that social media marketing has a positive and significant effect on purchase intention, social media marketing positively and significantly influences brand image, brand image positively and significantly affects purchase intention, and brand image can partially mediate (complementary partial mediation) the influence of social media marketing on purchase intention among prospective Adidas sports sneaker consumers in Denpasar. The implications of this study are divided into theoretical and practical aspects. Theoretically, the results support consumer behavior theory, suggesting that consumer behavior in developing purchase intention is influenced by various received information. Practically, if consumer perceptions of social media marketing for Adidas sports sneaker products are favorable, the brand image will improve, thereby increasing the purchase intention of prospective Adidas sports sneaker consumers in Denpasar.